Healthy Mouth, Healthy Lungs: Novel Solutions for Preventing and Diagnosing Periodontal Disease in the Context of Chronic Respiratory Illness - Anuj Singh Parihar; S Vinayak Agarwal; Dimple Narendra Lalwani; Asutosh Das; Meenakshi Boddun; Rashmi Laddha (Journal of Pharmacy and Bioallied Sciences)
Chronic respiratory illnesses, such as chronic obstructive pulmonary disease and asthma, pose significant challenges to public health worldwide. Mounting evidence suggests a bidirectional relationship between respiratory health and oral health, with periodontal disease emerging as a potential risk factor for the development and exacerbation of respiratory conditions. This review paper explores the complex interplay between periodontal disease and chronic respiratory illness, highlighting the importance of oral health maintenance in promoting respiratory well-being. By examining recent advancements in the prevention and diagnosis of periodontal disease, particularly in the context of chronic respiratory conditions, this paper aims to elucidate novel solutions and strategies for improving oral health outcomes and respiratory outcomes simultaneously. Through a comprehensive analysis of the literature and emerging research trends, this review sheds light on the potential benefits and challenges of integrating oral health into the management of chronic respiratory illnesses and identifies opportunities for future research and clinical practice.